Development of Application Based Football Learning - Amir Supriadi; Mesnan Mesnan (UNIB Press, 2022)
The method used in this research is to use R & D research methods used to develop products in the form of applicationbased soccer learning devices. The subjects in this study involved students from the sports science faculty (FIK) with a small scale trial involving 20 students of sports coaching education (PKO) and a large scale trial involving 40 creative and recreational physical education students (PJKR). The results of the assessments of 3 experts showed the results of 93% assessments of learning experts, 93% of media experts' assessments and 90% of soccer lecturers. The results of the small group trial showed a percentage of 88%, the large group trial showed a percentage of 90%. The conclusion in this study is that the development of application-based soccer learning is feasible to be used as a support in soccer learning.